No evidence of the unfolded protein response in the placenta of two rodent models of preeclampsia and intrauterine growth restriction - Denkl, Barbara; Cordasic, Nada; Hübner, Hanna; Menendez-Castro, Carlos; Schmidt, Marius; Mocker, Alexander; Wölfle, Joachim; Hartner, Andrea; Fahlbusch, Fabian (Biology of Reproduction, 2021)
In humans, intrauterine growth restriction (IUGR) and preeclampsia (PE) are associated with induction of the unfolded protein response (UPR) and increased placental endoplasmic reticulum (ER) stress. Especially in PE, oxidative stress occurs relative to the severity of maternal vascular underperfusion (MVU) of the placental bed. On the premise that understanding the mechanisms of placental dysfunction could lead to targeted therapeutic options for human IUGR and PE, we investigated the roles of the placental UPR and oxidative stress in two rodent models of these human gestational pathologies. We employed a rat IUGR model of gestational maternal protein restriction, as well as an endothelial nitric oxide synthase knockout mouse model (eNOS-/-) of PE/IUGR. Placental expression of UPR members was analyzed via qRT-PCR (Grp78, Calnexin, Perk, Chop, Atf6, and Ern1), immunohistochemistry, and Western blotting (Calnexin, ATF6, GRP78, CHOP, phospho-eIF2α, and phospho-IRE1). Oxidative stress was determined via Western blotting (3-nitrotyrosine and 4-hydroxy-2-nonenal). Both animal models showed a significant reduction of fetal and placental weight. These effects did not induce placental UPR. In contrast to human data, results from our rodent models suggest retention of placental plasticity in the setting of ER stress under an adverse gestational environment. Oxidative stress was significantly increased only in female IUGR rat placentas, suggesting a sexually dimorphic response to maternal malnutrition. Our study advances understanding of the involvement of the placental UPR in IUGR and PE. Moreover, it emphasizes the appropriate choice of animal models researching various aspects of these pregnancy complications.
CRIS-Team Scopus Importer:2021-08-27
Keywords: eNOS; ER stress; IUGR; oxidative stress; placenta; preeclampsia